Mathematics anxiety and students mathematical representation ability within a technology supported compassion based mathematics learning environment - Rustam; Nurfatin, Nafisa; Bistari (Universitas Islam Raden Intan Lampung, INDONESIA, 2026)
Purpose: This study aims to examine the relationship between mathematics anxiety and students’ mathematical representation ability within a compassion-based and technology-supported mathematics learning environment at the elementary school level. The research addresses the limited empirical evidence integrating affective and cognitive dimensions of mathematics learning in a single analytical framework. Method: A quantitative exploratory correlational design was employed involving 22 sixth-grade students from an elementary school in Indonesia. Participants experienced mathematics instruction implemented through a compassion-based approach supported by instructional technology. Data were collected using a mathematics anxiety questionnaire, an essay-based mathematical representation test assessing verbal, symbolic, and visual representations, and a compassionate learning perception scale. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM), complemented by descriptive statistical analysis. Findings: The results indicate that students demonstrated relatively high levels of mathematics anxiety, while their mathematical representation ability ranged from low to moderate with notable individual variation. Mathematics anxiety was strongly associated with students’ perceptions of a compassionate learning environment; however, the structural relationships among the studied variables were not statistically significant. Significance: This study provides preliminary empirical insight into the interaction between affective and cognitive factors in mathematics learning within a compassion-oriented and technology-supported context. The findings underscore the importance of integrating emotional support and instructional technology in mathematics education and suggest the need for further research with larger samples and extended intervention periods.